A Case Report on Tamak Swasa on the Effectiveness on Ayurvedic Medicine and Panchkarama in Children - Parnika Singh; N Sujatha (AYUSHDHARA, 2025)
Tamak Swasa, a respiratory condition described in traditional Ayurvedic medicine, is characterized by chronic cough, wheezing, and shortness of breath. This case study explores Tamak Swasa in a paediatric population, analyzing its prevalence, symptomatology, and management strategies. Whereas in ayurveda it is considered mainly Vata kapha prakopak. Ayurvedic treatment primarily focus on symptom relief and slowing the progression through Conventional methods. Objectives- To assess the effectives of integrated treatment approach in the management of Tamaka swasa using Shamana oushadies and Kunjal kriya in children. Methods- The 5 year old patient came to Kaumarbhritya OPD of PACH, Haridwar with complaints of recurrent attacks of severe cough and cold more in nights with attacks of dyspnoea since 2021.Parents approached child specialist who prescribed antibiotics, antiallergic, inhaler initially but he got no relief. Here we treated him with Ayurvedic medicines like Swasari and Mulethi kwath, Swasari vati, Laxmivilas ras and Shad bindu tail for Nasya along with mild form of Kunjal kriya (medicated water with salt + fennel) followed by Urovasti & Nadiswedan for 7days. Result - Patient showed significant relief symptomatically and his steroid inhalers were stopped completely after this Panchkarma therapy. Conclusion- The case study highlights the relevance of Ayurvedic medicine and therapies in managing Tamak Swasa in children. The integration of Ayurvedic practices demonstrated effective symptom control and improvement in respiratory function. This approach underscores the potential for incorporating traditional medicine in paediatric care, offering a complementary strategy for managing chronic respiratory conditions.